2017
DOI: 10.1039/c7ta01616f
|View full text |Cite
|
Sign up to set email alerts
|

Pore structure–CO2 adsorption property relations of supported amine materials with multi-pore networks

Abstract: Conventional supported amine adsorbents to date are known to suffer from the trade-off between increasing amine content and decreasing access to amine sites. To address this challenge size selection of loaded amines may be a useful tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…When the amine occupied too much of the available pore space, we found the diffusion of CO 2 molecules through the pores significantly inhibited, leading to a decrease in working CO 2 capture capacity . A recent study by our group investigated the trade-off not only between amine loading and amine efficiencies but also between CO 2 capture capacity and sorption kinetics of the supported amine adsorbents …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…When the amine occupied too much of the available pore space, we found the diffusion of CO 2 molecules through the pores significantly inhibited, leading to a decrease in working CO 2 capture capacity . A recent study by our group investigated the trade-off not only between amine loading and amine efficiencies but also between CO 2 capture capacity and sorption kinetics of the supported amine adsorbents …”
Section: Introductionmentioning
confidence: 87%
“…47 A recent study by our group investigated the trade-off not only between amine loading and amine efficiencies but also between CO 2 capture capacity and sorption kinetics of the supported amine adsorbents. 48 Herein, we present a novel bottom-up approach for the synthesis of an unprecedented MOF nanosheet with unusual and highly desired tunable thickness that self-organizes into a unique three-dimensional supramolecular coordination material (NEU-1) with tailorable porosity. Our approach opens the door to new MOF nanosheets and unique hierarchical supramolecular metal−organic frameworks with tunable pore systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the tailoring of nano pore structure and amine assembly is promising for improving the sorption and desorption kinetics of solid CO2 sorbents. Currently, much attention is focused on the tailoring of nano pore structure of supports and it is found that large pore size, large pore volume, short pore length, and three-dimensional (3D) connection of nano pores can reduce the diffusion limitation for CO2 [14,[20][21][22][23][24][25]. However, most studies focused on tailoring of the pore structure are aiming to mainly modifying the pore size and pore volume of cylindrical pores: Therefore, the design of pore shape to further modify the loading of organic amines in pores, which is also important for releasing free pore space along with the modifying of pore properties, should also be considered and remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…It also can be found that the carrier material with three-dimensional hierarchical pore structure overcomes the limitations of single mesoporous material and fully utilizes the advantages of various pore sizes. Simultaneously, large pore volume can accommodate more amine species and large surface area contributes to the fine dispersion of amine materials . Large pore size can prevent organic amines from blocking the support pores, and structural mesopores can reduce the CO 2 diffusion resistance in the support.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, large pore volume can accommodate more amine species and large surface area contributes to the fine dispersion of amine materials. 41 Large pore size can prevent organic amines from blocking the support pores, and structural mesopores can reduce the CO 2 diffusion resistance in the support. Simultaneously, we noted that the mesocellular silica foam (MCF) is a foamy mesoporous silica material with larger pore volumes and makes up of uniform spherical cells and windows.…”
Section: Introductionmentioning
confidence: 99%